Second line with oxaliplatin- or irinotecan-based chemotherapy for gemcitabine-pretreated pancreatic cancer: A systematic review. (August 2017) - Petrelli, Fausto; Inno, Alessandro; Ghidini, Antonio; Rimassa, Lorenza; Tomasello, Gianluca; Labianca, Roberto; Barni, Sandro; ,
Abstract: Background: oxaliplatin (OXA)- and irinotecan (IRI)-based chemotherapies are the most frequently used salvage regimens in patients with metastatic pancreatic cancer (PC) after first-line gemcitabine-based therapy. There are no prospective comparisons of these regimens in this setting. We conducted a systematic review of published trials to compare the efficacy of these treatments. Methods: studies that enrolled patients with stage IV disease receiving chemotherapy with OXA or IRI plus fluoropyrimidines were identified using electronic databases (Pubmed, Embase, SCOPUS, CINAHL, Web of Science and Cochrane Library). Clinical outcomes were compared using weighted values of median overall survival (OS), progression-free survival (PFS), response rates (RRs), and clinical benefit rates (CBRs). A 2-tailed t -test with a significance level of 0.05 for comparisons of continuous variables and a Chi-squared test for comparisons of proportions were used. Results: overall, 24 studies were included. The pooled overall response rate (ORR), disease control rate (DCR), PFS and OS were 11%, 37.9%, 2.87 and 5.48 months respectively. There was no significant difference in response rates between OXA-based and IRI-based chemotherapies (11.9% versus 8.7%; Chi-squared P = 0.1), respectively. Also there was no significant difference in median PFS (2.9 months versus 2.7 months; t -test P = 0.72), OS (5.3 months versus 5.5 months; t -test P = 0.72), but a greater DCR with OXA-based chemotherapy (41.1% versus 29.4%; Chi-squared P = 0.0008). Conclusion: OXA- and IRI-containing regimens were associated with similar efficacy when used after gemcitabine-based chemotherapy in patients with advanced pancreatic cancer. Highlights: Oxaliplatin and irinotecan-based regimens are the most frequent salvage chemotherapies for metastatic pancreatic cancer. No significant difference in response rates, PFS and OS was shown between oxaliplatin- and irinotecan-based regimens. Both regimens were associated with similar efficacy when used after first-line gemcitabine-based chemotherapy.